Physical Activity and Quality of Life in Retinitis Pigmentosa - Joshua D. Levinson; Ethan Joseph; Laura A. Ward; Joe R. Nocera; Machelle T. Pardue; Beau B. Bruce; Jiong Yan (Journal of Ophthalmology)
Purpose. Aerobic exercise has been found to be neuroprotective in animal models of retinal degeneration. This study aims to report physical activity levels in patients with RP and investigate the relationship between physical activity and vision-related quality-of-life (QOL). Materials and Methods. A retrospective study of adult patients with RP examined in 2005–2014. Physical activity levels were assessed using the Godin Exercise Questionnaire. The NEI-Visual Function Questionaire-25 (VFQ-25), SF-36 General Health survey, and Pepper Assessment Tool for Disability (PAT-D) were administered. Results. 143 patients participated. 81 (56.6%) patients were classified as “active” and 62 (43.4%) as “insufficiently active” by Godin score. VFQ-25 revealed statistically significant differences between the active and insufficiently active patients, including overall visual function (53.3 versus 45.1, p=0.010), color vision (73.8 versus 52.9, p<0.001), and peripheral vision (34.3 versus 23.8, p=0.021). The physical component of the SF-36 and the PAT-D survey also demonstrated statistically significant differences (47.2 versus 52.9, p=0.002; 24.3 versus 30.0, p=0.010). Active patients had a higher initial Goldmann visual field (GVF) score (74.8 versus 60.1 degrees, p=0.255) and final GVF score (78.7 versus 47.1 degrees, p=0.069) but did not reach statistical significance. Conclusions. In RP, increased physical activity is associated with greater self-reported visual function and QOL.